Benchmarking of Low-Field MR-Linacs in a Multi-Institutional International Consortium - Glide\\-Hurst, C.; Yadav, P.; Gutierrez, A.; Gungor, G.; Hoffmans, D.; Mittauer, K.; Sethi, A.; Romaguera, T.; Pennell, R.; Palacios, M.; Omari, E.; Meeks, S.; et al. (WILEY, 2019)
Annual Meeting of the American-Association-of-Physicists-in-Medicine (AAPM), San Antonio, TX, JUL 14-18, 2019